Psalm 44 : when God is responsible for suffering - Mare, Leonard P. (Journal for Semitics, 2012)
To be human is to experience suffering. Suffering impacts people on all levels of society. The question is: Why do humans suffer? It seems that at one level Israel believed that they ought not to suffer. They believed that if they stayed faithful to the covenant with God, then suffering should not happen. If they transgressed then suffering was to be expected. Deuteronomistic covenant theology and retribution theory reinforced this worldview. Yet, in Psalm 44, a different picture emerges. Israel celebrates the glorious deeds of salvation that God accomplished on their behalf. He delivered them through his mighty hand and brought them into the land of promise. Their current situation stands in sharp contrast to their past. To make matters worse, they suffer, not because they transgressed, but because God has rejected them. They are innocent, and God is to blame for their suffering. As such, Psalm 44 offers a protest against Deuteronomistic covenant theology and retribution theory, and places the blame squarely on God's shoulders.
free